Effect of Macroeconomic Variables and Tax Rates on the Six ASEAN Countries Tax Ratio - Effria Wijayanti Wahyuningsih; Milla Sepliana Setyowaty (Jurnal Administrasi Publik (Public Administration Journal), 2020)
The tax sector supports a stable process of economic growth and the tax ratio is considered an indicator that can be used to assess the performance of the taxation sector. This study examines the impact of macroeconomic and tax rates on the magnitude of the tax ratio in the case of six ASEAN member countries during the period 1998 to 2018. Data processing was performed using panel data regression using the Generalized Least Square (GLS) method with the STATA program. This study has very interesting results because inflation has a significant influence on the level of a country's tax ratio. The relationship between inflation and taxes is said to be positive, so any increase or decrease in inflation will also cause an increase or decrease also in the taxation sector. In other words, inflation and taxes move in the same direction but with different magnitudes. Countries with a stable macroeconomic situation will create greater opportunities for investment and more jobs are created. This will further increase the purchasing power of consumers and assume the tax burden will be easy for the public